Writing the Elusive Narrative of Soweto-Based Community Theatre, 1984–1994 - Xaba, Andile (Journal of Literary Studies, 2022)
The focus of the article is on writing the history of community theatre, which was a popular avenue for artistic expression for a number of township playwrights. During the period 1984–1994, there was a flowering of the arts in Soweto. Numerous popular community plays were staged, but this has not been documented due to a lack of record-keeping by the playwrights and the absence of formal theatre structures for township-based playwrights. In contemporary writing, theatre received attention from newspapers, with Gibson Kente, Matsemela Manaka and Maishe Maponya being the most prominent playwrights. Because of their popularity in South Africa and esteem with international audiences, the stature of the three playwrights presents an opportunity to see how a history of Soweto community theatre may be written. This article proposes that memory studies facilitates the writing of a more comprehensive narrative because it enables the melding of various sources: newspaper articles, theatre programmes, private archives, and information and insights from interviewees. Halbwachs’s methodology allows for a discussion in which theory (memory studies) and practice (writing the narrative) present evidence that community theatre has contributed to the development of theatre in South Africa. Without discounting the significance of (written) history, Halbwachs foregrounds the importance of memory, which resides with “people still living,” as key to formulating a narrative of the past. This is pertinent to Soweto community theatre, since the insights from interviewees and various sources also help to re-examine the perceived limitations attached to the label “community theatre.”